Social And Cognitive Factors Affecting Students’ Achievement in Using M-Reader - Chandra Andrean; Ikhsanudin; Dwi Riyanti (LPPM Universitas Advent Indonesia, 2026)
This study aims to investigate the social and cognitive factors that influence students' achievement in using M-reader, a mobile reading application. The study was conducted using a descriptive quantitative design, which involves collecting and analyzing data to know the social and cognitive factors affecting students’ achievement, the level of affection and how the factors affect students’ achievement in using M-reader. The data were derived from online questionnaires and interviews. The study involved collecting data from thirty students from the Sociology study program who are using M-reader for their English subject. This study concluded there were several subfactors that included in the social and cognitive factors. The level of affection from social and cognitive factors were in the trend of high to highest. In addition, social and cognitive factors developed students’ awareness and help them in achieving certain number of words in using M-Reader. Keywords: social factors, cognitive factors, M-Reader.